Practice of self- regulated learning in a blended learning environment among postgraduate students in higher learning setting / Zairrienoor Zairrin Zainudin - Zainudin, Zairrienoor Zairrin (2015)
Learning at postgraduate level yields different kind of challenges. It is an extra responsibility in adult life. It was reported that some postgraduate students fail to complete their study due to work and family issues. Self-regulated learning is one of the ways that can help postgraduate students to balance between all these responsibilities. This study seeks to find the practice of self-regulated learning among postgraduate students in a blended learning environment. The aims of this study are; to identify the practices of selfregulated learning in postgraduate study, to identify ways students regulate their learning in a blended learning environment and to investigate the problems and challenges emerged in postgraduate study. It was conducted in Klang Valley and as many as 23 postgraduates and former postgraduates took part. This study utilized a modified Self-Regulated Learning Interview Schedule (SRLIS). The finding is rather conclusive. However, it provides minformation that to a certain extent, students do practice SRL in their learning. Among of the problems faced are in regard with work, time management, study and others. Challenges comes from these angles; personal issues, academic and financial. It is hoped that this study could provide better understanding of the dynamic of postgraduates’ SRL practice in blended learning environment.